The Influence of Education Level and Family Support on Diet in People at Risk of Hypertension Using the Self Care Theory Approach - Dian Eka Resty (PT.Mantaya Idea Batara, 2025)
Hypertension is one of the diseases that increases every year Diet at the risk of hypertension is still not carried out because many hypertensive patients still have poor dietary behavior. The purpose of this study was to analyze the effect of education level and family support on diet in people at risk of hypertension with the Self Care theory approach. This case report method uses analytic observation by taking data on the level of education and family support using a questionnaire sheet as many as 80 respondents in outpatient X Lampung Hospital. The results showed that the variable that most influenced diet in people at risk of hypertension was family support with a value of (0.001) with a coefficient of - .420. Based on this, it can be seen that family support can affect diet in people at risk of hypertension, so it is necessary to have family support in people at risk of hypertension to reduce the risk of hypertension in people with risk of hypertension.